Chemotherapy-Induced Amenorrhea and Its Prognostic Significance in Premenopausal Women With Breast Cancer: An Updated Meta-Analysis - Wang, Yifei; Li, Yaming; Liang, Jingshu; Zhang, Nan; Yang, Qifeng (Frontiers in Oncology, 2022)
Objective: Chemotherapy-induced amenorrhea (CIA) is one of the most common side effects in premenopausal patients with breast cancer and several factors may contribute to the incidence of CIA. In this meta-analysis, we aimed to summarize clinical risk factors associated with CIA incidence and to evaluate their prognostic effects in patients with breast cancer. Methods: Three electronic databases (Cochrane Library, EMBASE, and MEDLINE) were systematically searched for articles published up to October 2021. The articles included clinical trials that evaluated risk factors associated with CIA and their prognostic value in treatment. For the meta-analysis, pooled odds ratio estimates (ORs) and 95% confidence intervals (CIs) were calculated using the inverse variance weighted approach, in addition to publication bias and chi-square test. Results: A total of 68 studies involving 26,585 patients with breast cancer were included in this meta-analysis, and 16,927 patients developed CIA. From the 68 studies, 7 risk factors were included such as age group, hormone receptor (HR) status, estrogen receptor (ER) status, progesterone receptor (PR) status, tamoxifen administration, chemotherapeutic regimen, and tumor stage. Based on our results, patients with age of ≤40, HR-negative status, ER-negative status, PR-negative status, no use of tamoxifen, use of anthracycline-based regimen (A) compared with anthracycline-taxane-based regimen (A+T) were associated with less incidence of CIA in patients with breast cancer. Moreover, CIA was associated with favorable disease-free survival (OR = 0.595, 95%CI = 0.537 to 0.658, P <0.001) and overall survival (OR = 0.547, 95%CI = 0.454–0.660, P <0.001) in premenopausal patients with breast cancer. Conclusion: Age, HR status, ER status, PR status, tamoxifen administration, and chemotherapeutic regimen can be considered independent factors to predict the occurrence of CIA. CIA is a favorable prognostic factor in premenopausal patients with breast cancer. CIA should be a trade-off in the clinical management of premenopausal patients with breast cancer and further large cohort studies are necessary to confirm these results.